Sistema obrazovanija v Rossii - Belova, Natalia (Vestnik za tuje jezike, 2010)
The Soviet educational system was considerably different from the educational system in Western Europe. In recent years, however, much has changed in the Russian educational system, especially after Russia joined the Bologna process in 2003. These changes are being reflected in different ways. On the one hand, the unification of Russian and European educational systems provides better opportunities for students. On the other hand, keeping track of all these newly introduced changes is not an easy task. Over the course of the last two decades, new types of educational institutions have been introduced in Russia (lyceums, gymnasiums, colleges etc.). The period of compulsory education has been extended to eleven years, and many institutions for higher education have introduced bachelor's and master's degrees. In this paper the main stages and the length of formal education in Russia are presented.
Keywords: Rusija; izobraževalni sistem; izobraževanje; education